Kandungan Rhodamine B pada Cabe Giling yang di Jual di Pasar Angso Duo dan Pasar Baru Kota Jambi - Zunidra Zunidra; Rina Fauziah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the presence or absence of Rhodamine B content in ground chilies sold at Angso Duo Market and Pasar Baru Jambi City and to determine the percentage of ground chilies that use and do not use Rhodamine B at Angso Duo Market and Pasar Baru Jambi City. The research design was an observational descriptive involving 40 samples of ground chili sold at Angso Duo Market and Pasar Baru, Jambi City. The results showed that the results of examining 40 samples of ground chili obtained positive results of ground chili containing 2 (5%) of Rhodamine B, while negative ground chili had 38 (95%) of rhodamine B. In conclusion, most ground chilies at Angso Duo Market and Pasar Baru Jambi City do not contain Rhodamine B. Keywords: Ground Chilli, Market, Rhodamine B